Study of Radionuclide Present in Air and Water Around Narora Atomic Power Station (NAPS), Uttar Pradesh, India (International Journal of Food and Nutritional Sciences, 2022)
In the present study, efforts have been made to estimate the natural radionuclide present in air and water samples in 3Km range around NAPS. The radioactivity level gamma rays in atmosphere in the 15 sites around NAPS in 3Km range were analyzed using “Digital Geiger Muller Counter Nuclear Radiation Detector Model: GQ GMC-300E Plus”. The results indicate that ambient gamma dose rates at the sites of study varied in the range 0.4671875Bq to 0.95234375Bq and found within the safety range of 1.796875Bq as per United States Environment Protection Agency recommendations. It depicts that overall air of study region around NAPS is found within the safe range of radiological risk and is not harmfully affecting the environment. The water samples were analyzed for the concentration of the uranium using the L.E.D. fluorim0eter Quantalase LF-2. This fluorimeter measures the uranium concentration in water samples from 0.5????????/???? to 1000????????/????. The concentration of the uranium was found to be varying in a range of 10.58 ????????/???? to 48.12????????/????. These findings of the study may provide valuable information about radioactivity in air environment and uranium concentration in the ground water samples of study area around NAPS.